La participación virtual de las familias en el centro educativo - Linde-Valenzuela, Teresa Loreto (UMA Editorial, 2019)
This research project is based on ecological and systemic paradigm of human development (Bronferbrenner, 1979). The theory of environmental system related to it, which influences the people, emphasizes the importance of context in order to produce changes in their evolutionary development, particularly in family relationships. This work has been addressed from exploratory and descriptive methodological treatment, which is studying groups of people in order to analyse concordances, discrepancies, peculiarities…, and for describing the reality of the facts subject of study from the context in which they are been produced. The study aims to know about virtual participation of the family in school centres, so measures and actions activated in centres, preservice and inservice digital training for teachers, families and pupils will be studied, teacher perception of this own training for relating to families, and interest of families to receive information and training. The research is structured in three sections: The first chapter, the theoretical framework, which addresses the issue, the desires aims and the reasons therefore, as well as the state of play on the topic covered in it. The second one, the empirical framework, which shows the methods used in pursuit of the achievement of objectives, is framed within a positivist paradigm and a qualitative one, with a mixed approach (mixed methods). The third chapter, conclusions and discussion on the issues raised at the beginning of the study, setting future research areas in reference to this work and improvement proposals to continue research in this field. Conclusions evidence the real situation of measures and activities which are working in the centres towards the virtual participation of families, the competences of teachers to relate to families and teachers’ competences to use and consume of ICTs, in addition of families’ interest to get information and training from the school centres.
Fecha de lectura de Tesis Doctoral: 23 de julio 2019.
Keywords: Familia y escuela; Organización escolar; Comunicación familia-escuela; Participación virtual; Competencia digital; Formación del profesorado; Planes de estudios